2010
DOI: 10.1186/1477-7827-8-117
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol, progesterone, testosterone profiles in human follicular fluid and cultured granulosa cells from luteinized pre-ovulatory follicles

Abstract: BackgroundThe production of sex steroids by follicular cells is proposed to be influenced by the maturity of the incumbent oocyte. Thus steroid levels may reflect suitability of an oocyte for IVF. We examined follicular fluids and granulosa cell production of steroid from IVF patients in order to test the relationship between steroid levels and fertilization.MethodsFollicular fluid and granulosa cells were extracted from 206 follicles of 35 women undergoing controlled ovarian stimulation. Follicular fluid was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 38 publications
1
59
1
1
Order By: Relevance
“…Similarly, it has recently been shown that androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA expression in human granulosa cells from small antral follicles [21]. Androgens also increase insulin-like growth factor 1 (IGF-1) expression in the primate ovary, which plays an essential role in regulating follicular development [22][23][24]. In mechanism, basal serum testosterone may have the patient for predicting ovarian response.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has recently been shown that androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA expression in human granulosa cells from small antral follicles [21]. Androgens also increase insulin-like growth factor 1 (IGF-1) expression in the primate ovary, which plays an essential role in regulating follicular development [22][23][24]. In mechanism, basal serum testosterone may have the patient for predicting ovarian response.…”
Section: Discussionmentioning
confidence: 99%
“…E 2 and P 4 are two of the main steroid hormones that play essential roles during follicular development. The fate of follicles is then determined by the balance between/ among these factors, and it is believed that E 2 and P 4 play vital roles during the process of folliculogenesis (Kezele & Skinner 2003, Wen et al 2010. Our findings may provide further insight into understanding these processes.…”
Section: Status Healthy Apoptoticmentioning
confidence: 60%
“…Even though there was a theory about androgenic intra-follicular environment may lead to follicle atresia, it was also known that a certain value of intra-follicular androgen levels needed for an optimal growth of follicles [1,4,10]. Wen et al (2010) [10] stated that a higher level of steroids will be found on follicles with more mature oocytes and better fertilization rate.…”
Section: Resultsmentioning
confidence: 99%